PENINGKATAN LITERASI SISWA KELAS V SDN 1 KADIPATEN PONOROGO MELALUI METODE PROBLEM BASED LEARNING (PBL) PADA PEMBELAJARAN BAHASA INDONESIA - Mellasari Arina Fajarini; Endang Sri Maruti; Arina Manasikana (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2023)
This study aims to develop literacy skills, especially when working on Indonesian language questions for students by using alternative solutions through the Problem Base Learning (PBL) learning model. The research approach used is classroom action research. This research is a class action research, by giving action to the subjects studied, namely fifth grade students at SDN 1 Kadipaten Ponorogo with 6 students consisting of 3 male students and 3 female students. When this research was carried out in the even semester of the 2022/2023 school year for 3 months, from March to May 2023. The results showed that through Problem Based Learning (PBL), students can learn to read and write contextually and meaningfully. They will also develop critical thinking skills, teamwork and creativity. The positive impact of the PBL method is also seen in students' ability to understand text, organize ideas, and optimize vocabulary mastery. Therefore, this method can be used as an effective alternative in increasing literacy in Indonesian lessons. Keywords: critical thinking skills, literacy skills, Problem Base Learning